(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Gastro intestinal (GI) diseases are common to cattle. These diseases give lots of pain and discomfort to the cattle and loss to the cattle keepers. Ayurvedic medicines have high potentiality in treating many non infectious GI disorders. In infectious GI diseases irrational use of antibiotics has increased the risk of resistance as well as side effects. There is a surge of search for alternative therapies and Ayurveda is believed to be the promised answer. In Andhra Pradesh many scholars and traditional physicians practiced Ayurvedic methods; medicines for the cattle treatment and few of them had dedicated their lives completely to Ayurvedic veterinary practice. They magnificently combined traditional wisdom of classical Ayurvedic texts with newly acquired knowledge from modern veterinary medicine. They used to diagnose the diseases on modern methods and treatment was given through Ayurvedic drugs. They recorded their treatment and research findings, documented and presented them in a systematic way for their publications. These publications are not available in public domains and they are protected by AP states archives, Hyderabad. These Telugu publications are unique to veterinary medicine. With lots of efforts and literary research the data is compiled and translated. Many GI diseases and there remedies are dealt in these publications and present paper deals the treatments of indigestion, painful condition due to indigestion, tympanites (abdominal distension), grain sickness (grain poisoning or acidosis), fardel-bound and colic., This article explores treatments in a scientific manner with suitable Botanical or English names of the plants along with dose in metric equivalents.